Military enlistment and attrition : an analysis of decision reversal - Antel, John J.; Hosek, James R.; Peterson, Christine E., 1954-; Defense Manpower Research Center; National Defense Research Institute (U.S.); Rand Corporation; United States. Office of the Assistant Secretary of Defense/Force Management and Personnel (Santa Monica, CA : RAND, 1987)
This report presents a theoretical discussion and empirical analysis of enlistment and first-term attrition. The theoretical discussion gives rise to hypotheses about enlistment and attrition. The enlistment hypotheses take a supply view, treating military service as an alternative to further schooling or to work. The attrition hypotheses are inherently two-sided, considering first the value of enlistment to the individual and the likelihood that he is more prone to disappointment due to poor planning, and second, the value of the individual to the service and the chance that the service's eligibility screens were unable to identify low-productivity prospects. The empirical analysis is directed to the two prime recruiting markets from which the services draw high-quality male enlistees: high school seniors and nonstudent high school graduates. The study estimates sequential probit models for seniors and graduates separately, for both enlistment and six-month attrition and enlistment and 35-month attrition. The model produces estimates of the effect of individual characteristics on enlistment and on attrition, and controls for unobserved factors affecting both outcomes. The findings suggest that a small set of factors can reveal a wide range of attrition risk among enlistees. The factors are senior/graduate status, positive/negative education expectations, stable/unstable civilian employment history, and short/long participation in the Delayed Entry Program.
"June 1987."
"National Defense Research Institute"--Cover.
This research was conducted "in RAND's Defense Manpower Research Center"--Preface.
Includes bibliographical references (p. 57-59).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: United States -- Armed Forces -- Personnel management; United States -- Armed Forces -- Recruiting, enlistment, etc